Building Religious Character of Students in Madrasah Through Moral Learning - Azhariah Rachman; Akhmad Nurul Kawakip; Fadhillah Fadhillah; Nanda Saputra; Zulkifli Zulkifli (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This article aims to describe the teacher's role and the implications of learning Aqidah Akhlak in the formation of the religious character of students at MTs Thoriqul Ulum Trawas. Qualitative with a case study approach has been used in this study. Data collection uses interview, observation, and documentation methods, while validity techniques use credibility, source triangulation, technical triangulation, and dependability. The results of the research are presented as follows: 1. Akhlak Aqidah teachers become motivators, mentors, and educators for students and are also less than optimal in their roles as facilitators and demonstrators. 2. The implications of Aqidah Akhlak teachers in forming the religious character of students at MTs Thoriqul Ulum, namely making students have the nature of discipline, responsibility, and honesty.